2002
DOI: 10.1038/nature01298
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 receptor regulates lifespan and resistance to oxidative stress in mice

Abstract: Studies in invertebrates have led to the identification of a number of genes that regulate lifespan, some of which encode components of the insulin or insulin-like signalling pathways. Examples include the related tyrosine kinase receptors InR (Drosophila melanogaster) and DAF-2 (Caenorhabditis elegans) that are homologues of the mammalian insulin-like growth factor type 1 receptor (IGF-1R). To investigate whether IGF-1R also controls longevity in mammals, we inactivated the IGF-1R gene in mice (Igf1r). Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

62
1,360
8
30

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,919 publications
(1,460 citation statements)
references
References 31 publications
62
1,360
8
30
Order By: Relevance
“…Diminished growth hormone/insulin‐like growth factor‐1 (GH/IGF‐1) signaling improves longevity across nature, including mice heterozygous for the IGF‐1 receptor (IGF‐1R) (Holzenberger et al ., 2003; Barzilai et al ., 2012). Moreover, low IGF‐1 action is relevant to humans because of its link to less cancer risk (Renehan et al ., 2004), an observation that spurred the development of IGF‐1R antagonists as a clinical cancer treatment (Pollak, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Diminished growth hormone/insulin‐like growth factor‐1 (GH/IGF‐1) signaling improves longevity across nature, including mice heterozygous for the IGF‐1 receptor (IGF‐1R) (Holzenberger et al ., 2003; Barzilai et al ., 2012). Moreover, low IGF‐1 action is relevant to humans because of its link to less cancer risk (Renehan et al ., 2004), an observation that spurred the development of IGF‐1R antagonists as a clinical cancer treatment (Pollak, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is not the first time a study was unable to replicate the increase in lifespan shown in an original study. For example, knockout mouse models for the signaling molecule p66Shc (p66shc −/− mice) (Migliaccio et al., 1999), insulin receptor substrate 2 (Irs2) (Irs2 +/− mice) (Taguchi, Wartschow & White, 2007), and the IGF1 receptor ( Igf1r +/− mice) (Holzenberger et al., 2003) all showed substantial lifespan extension in initial reports that was not confirmed in follow‐up studies (Bokov et al., 2011; Ladiges et al., 2009; Liang et al., 2003 ; Ramsey et al., 2014; Selman, Lingard, Gems, Partridge & Withers, 2008; Selman et al., 2007; Unnikrishnan, Deepa, Herd & Richardson, 2017). Differences in genetic background can potentially modulate lifespan results.…”
Section: Discussionmentioning
confidence: 88%
“…Pathways and mechanisms linked to both stress resistance and longevity include the insulin/IGF‐1 (Longo & Fabrizio, 2002) (Holzenberger et al ., 2003), TOR (Lin et al ., 2014) and NF‐κB (Helenius et al ., 1996) signaling pathways, DNA repair (Moskalev et al ., 2013), free radicals detoxication (Cutler, 2005), molecular chaperones (Morley & Morimoto, 2004), and epigenetic control of gene expression (Saunders & Verdin, 2009). In their recent review, Epel and Lithgow (Epel & Lithgow, 2014) suggested that reduction in stress resistance is a common feature for all of the nine hallmarks of aging proposed earlier by López‐Otín et al .…”
Section: Systematic Evaluation Criteria For Geroprotector Identificationmentioning
confidence: 99%